The Impact of Organizational cynicism in Job Engagement of Government Schools' teachers in Al Zubair district - صالح, رشا مهدي (Journal of Economics and Administrative Sciences, 2020)
The research aimed to investigate the level of Organizational Cynicism and Job Engagement of Government Schools teachers in Al Zubair district. To achieve this research was conducted on a random sample of (66) items. The statistical package for social sciences (SPSS) was used to analyze and examine the hypotheses. The researcher used many statistical methods to achieve the research objectives, such as simple, multi regression and the research results showed there is a significant impact to teacher's in the schools of the research sample between Organizational cynicism and Job  Engagement